Neurointerventional infusion of hemoglobin oxygen carrier prevents brain damage from acute cerebral ischemia in rats - Gao, Hong; Peng, Han; Yang, Hua; Li, Qiuping; Xiang, Xin (Frontiers in Surgery, 2023)
Aim To save brain cells in acute cerebral infarction by injecting hemoglobin oxygen carrier (HBOC) into the blood vessel blockage of the cerebral infarction site through a microcatheter. Methods 120 male rats were divided into four groups: control (CTRL), ischemia (I), ischemia + low perfusion (I + LP), and ischemia + high perfusion (I + HP). Perfusion groups (ischemia, I + LP, and I + HP) underwent MCAO surgery with intraluminal monofilament. These groups were subdivided into 6 h, 12 h, and 24 h (n = 10/group). RT-PCR, Western-Blot, immunohistochemistry, and apoptosis assays were used to detect apoptosis, hypoxia range and extent, and ischemia. Results Compared with the I group, the neurological deficit sign scores of the I + HP group were statistically significant at 12 h. Compared with the I group, the neurological deficit sign scores of the I + LP group and the I + HP group were statistically significant at 24 h. At all time points, compared with the I group and the I + LP group, Caspase-3, HIF-1α, and Cytochrome C protein levels were significantly decreased in the I + HP group. Bcl-2 and BAX mRNA levels were also significantly decreased in the same group. TNF-α, IL-6, and IL-1β cytokines were significantly decreased in the I + HP group as well. The infarct size of rats in the I + HP group was smaller than that of the I + LP group, which was smaller than ischemia alone. Time of perfusion had an obvious effect as infarct size was smaller with longer perfusion. The number of Nissl stained cells in the I + HP group was increased compared with the ischemia and the I + LP group, and was proportional to the time of perfusion. Conclusion Time- and rate-controlled perfusion of HBOC to acutely occluded cerebral vascular regions through microcatheters can effectively protect ischemic brain tissue in rats.